Knowledge based systems as an aid in information systems audit - Proaño Escalante, Rodrigo Arturo; Saguay Chafla, Ciro Napoleón; Jácome Canchig, Segundo Bolívar; Sandoval Zambrano, Fanny (Enfoque UTE, 2017)
One of the problems that the IT auditor has when expressing an opinion about a finding is the subjectivity that can be due to many aspects, among the main ones: emotional, technical skills or abilities with which this opinion can be right or wrong. This is a major problem because the audit report issued may have distortions of the facts. On the other hand, the development of the expert systems involves capturing the knowledge of the human and transferring it to a computer program in which all the characteristics of this knowledge are emulated and considering a group of rules, the system can make decisions as a human does. Advances in artificial intelligence over the last few years have led to the development of these knowledge-based systems increasing and the results obtained are more real. The use of these systems presents a promising future in the field of computer audit. The objective of this article is to give a general idea of the characterization and use of knowledge based systems, the way they are implemented and their application to the audit of information systems as a tool to help the opinion issue at the moment of realization of an audit.